Biorremediação de pesticida por consórcio fúngico - Cavalcante, Alyne Vasconcelos (2024)
An alternative for the remediation of areas contaminated by pesticides is the use ofmicroorganisms to remove chemical compounds. It is a consensus in the literature thatthere is a constant search for the isolation of consortia that promote the degradation of agreater quantity of complex pollutants such as pesticides, which contaminateenvironmental matrices like water, soil, and air. Thus, the aim of this research was toevaluate the ability of fungal species to remove pesticides in synthetic aqueous medium.The thesis was structured into four sections: 1) a general introduction, with a researchquestion and possible hypotheses; 2) a review article entitled "Potential of fungi for thebioremediation of pesticides: a review on isolated strains and consortia," which addressesthe main types of pesticides commonly studied in bioremediation research, as well as thestate of the art based on a literature review with inclusion and exclusion criteria. 3) anexperimental article entitled "Effect of pesticide on the growth of consortium fungi," inwhich the tolerance of the four studied species to the herbicide paraquat was evaluated atconcentrations of 10, 20, 30, 40, 50, and 60 mg.L-1. 140 plates were prepared forphotographic recording and for calculating the growth rate of isolated fungi andconsortium fungi. 4) an experimental article entitled "Fungal consortium for paraquatdegradation in reactors with dispersed and immobilized biomass," in which batch reactorswith dispersed biomass were set up, followed by sequential reactors with immobilizedbiomass in the absence and presence of co-substrate. The species chosen for the batchreactors were those that performed better in Petri dishes: Aspergillus niger AN 400,Phanerochaete chrysosporium, and Trametes versicolor. Based on the removal resultsfrom the batch reactors with dispersed biomass, the composition of the sequential reactorswas decided, which included a reactor with the A. niger and P. chrysosporium consortiumwithout glucose and a reactor with A. niger in the presence of 5 g.L-1 of glucose, in 10cycles of 48 hours each. The A. niger and P. chrysosporium consortium achieved 42%paraquat removal, while the A. niger isolated with glucose removed 37.3% of paraquatduring batch agitation. The results obtained in the sequential reactors indicated thefeasibility of using consortium fungi for pesticide removal in liquid media, with a focus onimproving reaction time. The parameters of paraquat removal, chemical oxygen demand,and pH were studied in all reactors. In the sequential batches, it was observed that theparaquat removal values did not follow a pattern.